2016
DOI: 10.1097/sap.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

Orange Peel Excision of Gland

Abstract: The technique has reduced operative time and avoids residual gland and hematoma with excellent aesthetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“… 8 , 17 , 19 , 23 , 24 , 26 Revision rate was specifically reported by 8 authors and ranged from 0% to 14.1%. 8 , 9 , 19 , 20 , 23 , 26 , 29 , 31 Hematoma was the most often cited major complication occurring in 5.8% of cases, which is consistent with what has been previously stated in the literature (4.6%). 10 , 11 Seroma formation was the next most common complication occurred in 2.4% of cases (Table 4 ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“… 8 , 17 , 19 , 23 , 24 , 26 Revision rate was specifically reported by 8 authors and ranged from 0% to 14.1%. 8 , 9 , 19 , 20 , 23 , 26 , 29 , 31 Hematoma was the most often cited major complication occurring in 5.8% of cases, which is consistent with what has been previously stated in the literature (4.6%). 10 , 11 Seroma formation was the next most common complication occurred in 2.4% of cases (Table 4 ).…”
Section: Resultssupporting
confidence: 90%
“…The majority of authors specifically listed standard use of drain placement in all patients regardless of surgical technique, with the exception of Wyrick et al (who reported drain usage based on surgeon preference), Li et al (who did not utilize drain placement in patients with grade I gynecomastia who received SSPM ± liposuction), and Shirol, Khalil et al, Coskun et al, Sim et al, and Akhtar et al (who did not routinely utilize drain placement in any patients). 8 , 9 , 17 , 20 , 23 , 24 , 26 31 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations